2009
DOI: 10.1111/j.1399-0012.2008.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of meticulous management for hepatic artery thrombosis on long‐term outcome after pediatric living donor liver transplantation*

Abstract: To analyze the risk factors in the development of hepatic artery thrombosis (HAT) and assess the impact of our perioperative management for HAT on the long-term outcome after pediatric living donor liver transplantation (LDLT), we reviewed 382 patients under 12 yr of age who underwent 403 LDLT from January 1996 to December 2005. One- and 10-yr patient survival rates were 78% and 78% in the patients with HAT (27 patients; 6.7%), and 84% and 76% in the patients without HAT, respectively (p = n.s.). Univariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 23 publications
3
63
0
Order By: Relevance
“…Figure 1 (12,28,42,51,52,71,73,76,77) for the arterial anastomosis (3.1%) versus centers using loupe magnification (2.1%, p = 0.6) (25,37,53,54,74).…”
Section: Results Of the Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 (12,28,42,51,52,71,73,76,77) for the arterial anastomosis (3.1%) versus centers using loupe magnification (2.1%, p = 0.6) (25,37,53,54,74).…”
Section: Results Of the Search Strategymentioning
confidence: 99%
“…In only two centers routine DUS was not performed (3,46 (12,27,28,33,42,44,48,51,52,54,62,65,71,84 (12,16,17,21,25,27,28,33,35,(41)(42)(43)(45)(46)(47)(48)(53)(54)(55)57,59,67,(70)(71)(72)(73)80,82,(84)(85)(86)(87) (12,27,28,33,42,…”
Section: Doppler Ultrasound Screening Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 We observed that female sex was associated with greater morbidity, similar to a previous study from Kyoto that reported that female sex and high GRWR were independent risk factors for hepatic artery thrombosis after LDLT. 28 To our knowledge, few studies have reported outcomes of ICU-bound pediatric patients after LDLT. [3][4][5] Hereby, in ICU-bound pediatric patients, bacterial infection was diagnosed in 63% patients, fungal infection was diagnosed in 7.4% patients, and viral infection was diagnosed in 28% patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, the authors report a combined HAT/PVT rate of < 3% in 110 transplants over 21 years. Evidence from other centers also supports the efficacy and safety of AT replacement and prophylactic anticoagulation [26,27]. In contrast, other authors avoid the routine use of anticoagulants, FFP or AT concentrates, arguing that surgical factors are the major variables contributing to thrombosis risk [28].…”
Section: Thromboprophylaxismentioning
confidence: 99%